Financial Development and Economic Growth: an Empirical Analysis of Indonesia - Muh Dularif (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2010)
This paper empirically investigates the relationship between financialdevelopment and economic growth in Indonesia. A vector autoregressive model using time series data between 1968 and 2009 presents this dynamic relationship. Financial depth, the role of commercial banks, and credit to private sectors are threemeasurements of financial development used in this paper. However, differing from much empirical research in developed countries in which financial systems are wellbehaved, the results of this research suggest that financial development in Indonesiadoes not have a significant positive impact on economic growth. The main factor in the failure of financial development in promoting growth is lack of fundamental factors in the financial system. These factors are lack of credibility of the monetary regulator, weaknesses in financial regulations and supervision, lack of a legal system and anignorance of good corporate governance in the financial sector. In particular, there is no evidence that financial liberalization will promote economic growth if it is done without the development of a strong financial system.